2006
DOI: 10.4049/jimmunol.177.11.8086
|View full text |Cite
|
Sign up to set email alerts
|

The Duffy Antigen Modifies Systemic and Local Tissue Chemokine Responses following Lipopolysaccharide Stimulation

Abstract: The Duffy blood group Ag (dfy) binds selective CXC and CC chemokines at high affinity and is expressed on erythrocytes and endothelial cells. However, it does not transmit a signal via G proteins, as occurs with other seven-transmembrane receptors. We hypothesized that dfy functions as a chemokine reservoir and regulates inflammation by altering soluble chemokine concentrations in the blood and tissue compartments. We determined whether Duffy Ag “loss-of-function” phenotypes (human and murine) are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 37 publications
6
79
0
1
Order By: Relevance
“…37 Supporting this, studies in mouse models show that DARC expression on both RBC and endothelial cells influences neutrophil migration. 38,39 In addition, DARC Ϫ46C/C may associate with impaired hematopoiesis because some of the chemokines that bind to DARC (eg, GRO␣ 40 ) regulate many hematopoietic responses, including survival, proliferation, migration, and homing. 41 Supporting this possibility, healthy subjects of African ancestry have reduced numbers of bone marrow progenitor cells than Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…37 Supporting this, studies in mouse models show that DARC expression on both RBC and endothelial cells influences neutrophil migration. 38,39 In addition, DARC Ϫ46C/C may associate with impaired hematopoiesis because some of the chemokines that bind to DARC (eg, GRO␣ 40 ) regulate many hematopoietic responses, including survival, proliferation, migration, and homing. 41 Supporting this possibility, healthy subjects of African ancestry have reduced numbers of bone marrow progenitor cells than Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…An exaggerated inflammatory response observed in the lungs and liver of DARC knockout mice is consistent with the idea that the molecule functions as a chemokine-clearing receptor (19). It has been suggested that DARC may limit the actions of chemokines and alter allergic inflammation (20,21).…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…However, it does not transmit a signal via G proteins, as occurs with other seven-transmembrane receptors. The receptor serves as a chemokine reservoir, regulating tissue and plasma chemokine levels, thus affecting neutrophil migration to various tissues, including the lung [80][81][82][83]. Mice deficient in this receptor demonstrate impaired neutrophil migration to the lung, intestines and peritoneum, and altered chemokine levels in the serum and tissue [82,83].…”
Section: Modification Of Chemokine Gradients In Alimentioning
confidence: 99%
“…The receptor serves as a chemokine reservoir, regulating tissue and plasma chemokine levels, thus affecting neutrophil migration to various tissues, including the lung [80][81][82][83]. Mice deficient in this receptor demonstrate impaired neutrophil migration to the lung, intestines and peritoneum, and altered chemokine levels in the serum and tissue [82,83]. In endothelial cells expressing the Duffy antigen, neutrophil migration toward GRO-α/CXCL1 and IL-8 (IL-8/CXCL8) was enhanced, suggesting that the Duffy antigen participates in the movement of neutrophil chemokines across the endothelium [81].…”
Section: Modification Of Chemokine Gradients In Alimentioning
confidence: 99%